The Impact of Environmental Social Governance (ESG) on Firm Performance with the Moderating Role of CEO Turnover - Ameliawati, Hertya Dwi; Hendranastiti, Nur Dhani (Graduate Program Magister Manajemen Pendidikan, 2024)
This research aims to investigate the influence of Environmental, Social, and Governance (ESG) on firm performance, measured by Return on Equity (ROE). Additionally, the study explores the moderating role of CEO turnover in the relationship between ESG and firm performance in publicly listed companies on the Indonesia Stock Exchange, with a sample of 33 companies from 2016 to 2022. The GMM estimator method is employed to address endogeneity issues, ensuring consistent and unbiased estimation results. Findings indicate that overall ESG performance significantly affects firm performance, emphasizing the importance of implementing ESG principles in Indonesian businesses to enhance ROE. Other results reveal the pure moderating role of CEO turnover, weakening the relationship between ESG and firm performance. Therefore, proper planning and guidelines for CEO succession are crucial for improving firm performance and sustainability. The research results carry important implications for Indonesian companies to consider ESG implementation in their business strategies. Furthermore, CEO succession planning management is key to maximizing the positive impact of ESG on firm performance. This study contributes to a deeper understanding of how ESG factors influence firm performance in the Indonesian business context, highlighting the significance of executive leadership in managing these impacts.